2021
DOI: 10.2319/020521-108.1
|View full text |Cite
|
Sign up to set email alerts
|

Smile microesthetics as perceived by dental professionals and laypersons

Abstract: Objectives To evaluate and compare the perception of different dental professionals and laypersons toward altered gingival characteristics (microesthetics) and to identify those characteristics that are most negatively and positively rated. Materials and Methods A smiling photograph of a female dental student was selected and digitally manipulated to create changes in different microesthetic parameters. These altered images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
1
15
2
Order By: Relevance
“…Gingival asymmetry can be treated by a multidisciplinary approach, but it is necessary to know how much asymmetry is acceptable to our patients. Previous studies showed that dental specialists were more critical of gingival asymmetries than laypersons ( 3 , 7 , 11 ). The results of our study are in agreement with these findings as we reported that specialists could detect 1 mm of gingival asymmetry, unlike laypeople who were unable to see gingival asymmetry less than 2 mm.…”
Section: Discussionmentioning
confidence: 98%
“…Gingival asymmetry can be treated by a multidisciplinary approach, but it is necessary to know how much asymmetry is acceptable to our patients. Previous studies showed that dental specialists were more critical of gingival asymmetries than laypersons ( 3 , 7 , 11 ). The results of our study are in agreement with these findings as we reported that specialists could detect 1 mm of gingival asymmetry, unlike laypeople who were unable to see gingival asymmetry less than 2 mm.…”
Section: Discussionmentioning
confidence: 98%
“…The researchers controlled the rating time, ensuring no comparison of photos and a fixed view distance for the purpose of reducing bias. Unlike Alomari et al [ 26 ], a study regarding smiles was done based on online google form questionnaires, making it difficult to control dimensions since the raters can zoom. While [ 28 , 29 ] gathered the raters in a classroom, the raters' location may have influenced their responses.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using G*Power (V. 3.1.9.4) based on a previous study that reported a mean attractiveness score of (2.22 ± 0.94) and (2.18 ± 0.81) by laypeople and orthodontists respectively, assuming a small effect size difference (0.25) between groups. The power analysis showed a total sample size estimate of 220 raters required for each ethnic group, with at least 45 participants for each group based on the profession at a conventional α level (0.05) and desired power (1 – β) of 0.85 [ 26 ]. This number was later increased to 280 for each ethnic group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might result in esthetic troubles, speech problems, food impaction and/or improper plaque control 5 7 . Black triangles, especially between the central incisors, are considered among the worst esthetic factors that negatively impact smile esthetics 8 12 .…”
Section: Introductionmentioning
confidence: 99%